PERUBAHAN BUDAYA PETANI TEPIAN HUTAN DALAM PENGEMBANGAN PENGELOLAAN SUMBERDAYA HUTAN BERBASIS MODAL SOSIAL CULTURAL CHANGES OF FOREST OUTSKIRT PEASANTS IN THE DEVELOPMENT OF FOREST RESOURCES MANAGEMENT BASED ON SOCIAL CAPITAL - Santoso, Imam (Pembangunan Pedesaan, 2007)
The researchâs result showed that there was differences between peasants with and without social capital in relation to its social and economic characteristics in forest resources management. The differences affected forest outskirt peasant behavior in utilizing forest resources. Peasants cultural changes in term of forest handling had been gradually happened evolutionarily. Peasants who have strong social capital tended to pay attention on forest conservation, but in contrast, peasant who has experienced social capital breakdown tended not to pay attention on forest resources degradation. The result implied that the transformation of peasants behaviour went from lower to higher social capital through analysis for formulating integration model of social capital growth on forest outskirt peasants in the effort of forest resources management.